Fiscal adjustment in Greece: In search for sustainable public finances - Bas van Aarle; Marcus Kappler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper analyses Greek fiscal sustainability from a retrospective and a prospective view. Implications of Greek fiscal (un)sustainability are discussed. In the empirical analysis econometric testing of Greek government solvency during the period 1985-2008 is combined with a scenario analysis of budgetary adjustments during the period 2011-2030 under alternative hypotheses.
Keywords: F31; F41; G15; 330; Greece; euro area; fiscal policy; policy rules; fiscal sustainability; Finanzpolitik; Nachhaltigkeit; Eurozone; Griechenland; Regelgebundene Politik; Griechenland